Effects of Oncoming Vehicle Size on Overtaking Judgments. (September 2014) - Levulis, Samuel J.; DeLucia, Patricia R.; Jupe, Jason
In 2011, 89, 000 accidents in the United States involved a vehicle passing another vehicle, which resulted in 740 deaths and 19, 000 injuries (NHTSA, 2011). When passing a vehicle on a two-way highway (overtaking), a driver often must temporarily cross into the opposite lane of traffic, and may face oncoming vehicles. To avoid a collision with an oncoming vehicle, the overtaking driver must estimate the time remaining until a collision would occur with the vehicle. Although information about an oncoming vehicle's time-to-collision is theoretically available in the optical invariant tau (Lee, 1976), it is below threshold during high-speed overtaking maneuvers, which require a large passing distance. Under such conditions, we expect drivers to rely on the oncoming vehicle's apparent distance and velocity, and thus depth cues such as relative size. We used a driving simulator to determine whether overtaking judgments are influenced by an oncoming vehicle's size, and on whether such judgments differ between active driving and passive viewing. Twenty-four participants viewed computer-generated scenes in which they were following a lead vehicle on a straight, two-lane, two-way highway. At the start of each scene an oncoming vehicle (motorcycle, car, delivery truck) was visible in the opposite lane. Seven seconds after the scene an auditory tone signaled participants to make an overtaking decision. Participants in the active condition passed the lead vehicle if they thought it was safe to do so. Participants in the passive condition indicated whether it was safe to pass by pressing buttons on the steering wheel. We manipulated the participant's (and lead vehicle's) speed (48.28 km/h, 64.37 km/h, 80.47 km/h) and the oncoming vehicle's speed (72.42 km/h, 88.51 km/h, 104.61 km/h) and distance when the tone occurred (457.20 m, 609.60 m). This resulted in 9 safe and 9 unsafe temporal gaps based on an equation generated from analyses of actual overtaking performance (Gordon & Mast, 1970). Results indicated more accepted gaps and more false alarms (accepted gap when unsafe) in front of motorcycles than larger cars or trucks. The judgments made by participants in the active and passive conditions did not differ. Analyses of signal detection theory measures of sensitivity (d-prime) and response bias (beta) suggested that the effect of vehicle size was due to shifts in response bias rather than sensitivity. Results have implications for traffic safety and for the potential role of driver-assistance technologies.